2012
DOI: 10.1002/asia.201200308
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Catalyzed Rauhut–Currier Domino Reaction: A Facile Strategy for the Construction of Highly Functionalized Cyclopentene

Abstract: New strategy: A novel phosphine‐catalyzed domino reaction of activated conjugated dienes and electron‐deficient olefins was developed. In this reaction, intermolecular Rauhut–Currier reaction was successfully incorporated in a domino process, and a variety of highly functionalized cyclopentenes were obtained in good yields and diastereoselectivities. Two new CC bonds were formed together with a quaternary carbon center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…As is shown in Scheme , Huang proposed that the 1,5‐zwitterion intermediates 47 might be trapped by intramolecular Michael addition to their active double bonds, with subsequent proton transfer processes delivering the final cycloaddition products 38. Under the above optimized conditions, the reactions between 2‐arylmethylidenemalononitriles and conjugated dienes37 gave the target cyclopentenes 63 (Scheme ) with high yields and stereoselectivities 38. Interestingly, use of benzoic acid as an additive could dramatically improve the yield and stereoselectivity.…”
Section: Domino Cyclization Initiated By Cross‐rauhut–currier Reacmentioning
confidence: 99%
“…As is shown in Scheme , Huang proposed that the 1,5‐zwitterion intermediates 47 might be trapped by intramolecular Michael addition to their active double bonds, with subsequent proton transfer processes delivering the final cycloaddition products 38. Under the above optimized conditions, the reactions between 2‐arylmethylidenemalononitriles and conjugated dienes37 gave the target cyclopentenes 63 (Scheme ) with high yields and stereoselectivities 38. Interestingly, use of benzoic acid as an additive could dramatically improve the yield and stereoselectivity.…”
Section: Domino Cyclization Initiated By Cross‐rauhut–currier Reacmentioning
confidence: 99%
“…Mp 85−88°C (yellow solid), 120 mg (97%); hexane−ethyl acetate90:10 (v/v, eluent); 1 H NMR (400 MHz, CDCl 3 ) δ 6.37 (d, J = 9.6 Hz, 1H), 7.15−7.38 (m, 10H), 7.46 (d, J = 9.6 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 114.0, 117.8, 127.9, 128.1, 128.9, 129.1, 129.2, 129.9, 132.0, 136.2, 147.8, 158.0, 161.7; HRMS m/z Calcd for C17 H 12 O 2 (M + ) 248.0837, found 248.0840. 5,6-Bis(4-methylphenyl)-2(2H)-pyran-2-one (3b).…”
mentioning
confidence: 99%
“…According to the experimental results and previous studies, [12,13,15] we proposed a possible mechanism that can help to account for the formation of carbocyclic spirooxindoles in this domino reaction (Scheme 4). According to the experimental results and previous studies, [12,13,15] we proposed a possible mechanism that can help to account for the formation of carbocyclic spirooxindoles in this domino reaction (Scheme 4).…”
mentioning
confidence: 74%
“…A number of conjugated dienes 1, either bearing electron-withdrawing or electron-donating substitutions on the aryl group, were converted smoothly when the N-protecting groups is Ac ( Table 2, entries 1-7). When isatin N-protecting acetyl groups is replaced with Boc, high yields could be obtained, albeit with slight lower stereoselectivities and reversed diastereoselectivity ( Table 2, entries [11][12][13][14]. Furthermore, it was observed that the steric hindrance of the ester sub-stituent has no effect on the result ( Table 2, entries 8-10 and 14).…”
mentioning
confidence: 99%
See 1 more Smart Citation